Counterintuitive consequences of COVID-19 on healthcare workers: A meta-analysis of the relationship between work engagement and job satisfaction - Yildiz, Bora; Yildiz, Tayfun; Ozbilgin, Mustafa; Yildiz, Harun (Frontiers in Psychology, 2022)
Background Studies conducted in the health sector have determined a positive relationship between job satisfaction and work engagement. However, this paper reveals that this relationship turns into a negative or non-significant relationship during the COVID-19 pandemic. We explore the reasons for inconsistency in research findings in this critical period through a meta-analysis. Methods This study was conducted according to the PRISMA guidelines and PICO framework. Online databases including Web of Science, Scopus, PubMed, ProQuest, Google Scholar, and additional records from other databases were searched without any time limitation, and all studies published in English that reported the correlation between work engagement and job satisfaction were included in the analysis. In total, 36 individual correlation coefficients were synthesized. R statistical language was used to analyze the data. Result A total of 36 studies with a sample size of 16,087 were synthesized. The overall effect size was found as r = 0.57 (95% CI [0.50–0.64]). While the moderating effect of national culture was not statistically significant, presence of COVID-19 as the significant moderator explained 37.08% of effect size heterogeneity. Such that the presence of COVID-19 has transformed the positive relationship between work engagement and job satisfaction into a negative but statistically non-significant relationship. Conclusion This study empirically challenges the existing assumptions about the positive link between work engagement and job satisfaction. The results of the research can be a guide for managers and policymakers. Specifically, based on these results, different mechanisms can be put in place to support work engagement and, in turn, job satisfaction in the COVID-19 process.